Effect of Animated Health Education on Adolescents’ Knowledge and Attitudes Toward Sexual Violence: A Time Series Study - Ririnisahawaitun; Sari, Apriani Susmita; Suhaemi, Suhaemi; Astuti, Baiq Lastri Zuhria (An Idea Health Journal, 2026)
Introduction: Adolescents are vulnerable to sexual violence. Violence affecting adolescents includes sexual violence in personal relationships, such as dating, and sexual violence against children, with perpetrators often being close family members. Additionally, community violence can occur between friends or in public locations. Health counseling on sexual violence can prevent this violence by enhancing adolescents’ knowledge and attitudes about sexual violence. The study aims to determine the effect of health education on adolescents’ knowledge and attitudes about sexual violence. This research is a quasi-experiment (pseudo-experiment) with a time series design. The sample was 32 students at SMPN 1 Sakra, which was determined by cluster random sampling, so class VIIIB was chosen as the research sample. Health counseling on sexual violence was provided with animated video media. Data processing with a paired t-test has tested the validity and reliability of instruments to measure adolescents’ knowledge and attitudes about sexual violence. This study’s results showed there is an effect of health education on adolescents’ knowledge and attitudes about sexual violence, with a p-value of 0.000 each, where there is an increase in adolescents’ knowledge about sexual violence after being given education, with the difference between pretest and posttest being 2.72. After receiving education, adolescents’ attitudes about sexual violence increase, showing a difference between the pretest and posttest of 3.75. The conclusion is that there is an effect of health education on adolescents’ knowledge and attitudes about sexual violence through animated video media.